2010
DOI: 10.1007/s10456-010-9183-z
|View full text |Cite
|
Sign up to set email alerts
|

The small molecule specific EphB4 kinase inhibitor NVP-BHG712 inhibits VEGF driven angiogenesis

Abstract: EphB4 and its cognitive ligand ephrinB2 play an important role in embryonic vessel development and vascular remodeling. In addition, several reports suggest that this receptor ligand pair is also involved in pathologic vessel formation in adults including tumor angiogenesis. Eph/ephrin signaling is a complex phenomena characterized by receptor forward signaling through the tyrosine kinase of the receptor and ephrin reverse signaling through various protein–protein interaction domains and phosphorylation motifs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
111
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(116 citation statements)
references
References 45 publications
4
111
1
Order By: Relevance
“…In addition to the identification of inhibitors targeting EphA2, efforts have been devoted to develop selective EphB4 RTK inhibitors (61) due to its prominent role in tumor angiogenesis. Of these, NVP-BHG712 has displayed relative selectivity towards EphB4, inhibiting its kinase activity in the nanomolar range in cell-based assays.…”
Section: Kinase Inhibitorsmentioning
confidence: 99%
“…In addition to the identification of inhibitors targeting EphA2, efforts have been devoted to develop selective EphB4 RTK inhibitors (61) due to its prominent role in tumor angiogenesis. Of these, NVP-BHG712 has displayed relative selectivity towards EphB4, inhibiting its kinase activity in the nanomolar range in cell-based assays.…”
Section: Kinase Inhibitorsmentioning
confidence: 99%
“…The model has been previously described [24][25][26]. Briefly, porous tissue chambers made of perfluoro-alkoxy-Teflon (Teflon Ò -PFA, 21 9 8 mm diameter, 550 ll volume) were filled with 0.8% agar (BBL Ò Nr.…”
Section: Animalsmentioning
confidence: 99%
“…growth factor implant angiogenesis model [24][25][26]. For this purpose, mice were implanted with Teflon chambers containing either VEGF or bFGF, two well known angiogenic factors, or PBS as a baseline control.…”
Section: Impaired Vegf-driven Angiogenesis In Gpr4-deficient Micementioning
confidence: 99%
“…In the primary human brain cancers that we studied, the expression of the components of the ephrinB system evaluated did not display a clear relationship with either grade or cancer type, EphrinB2 being the most highly expressed, but anyhow at low level and possibly only in the remaining nontumoral neural cells, reactive astrocytes or remaining neurons, of the cancer tissue. EPHB4 and EphrinB2 are necessary for vascular development, and for tumor angiogenesis, cross-talking with the VEGF system [1,3,19], however the role of EphrinB2 and EPHB4 in cancer cells is complex, paradoxical, and sometimes opposite. It has been shown that EPHB4 on tumor cells interact with EphrinB2 on endothelial cells, promoting angiogenesis, while EPHB4 may be important for tumor cell growth, either increasing or decreasing tumor growth depending on the context; for example, human colorectal cancers lose expression of EphB at the adenoma-carcinoma transition, correlated with cancer progression [20].…”
Section: Discussionmentioning
confidence: 99%